(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article is devoted to a comparative analysis of scientific relations to the English translations of Abdurauf Fitrat’s artistic works. It is discussed in the article that Abdurauf Fitrat’s artistic works were translated abroad by foreign scholars, including Shawn Thomas Lyons, a professor at the University of Virginia in America, Adib Khalid, a professor at Carleton University in America, and Salih Beshakci, a Turkish scholar into various languages, including English with great interest, and analyzed in depth. Also, in the article we try to analyze comparatively how they showed their own scientific attitudes towards them. Sometimes, the ideological content, artistic features of Fitrat’s works have also been drawn to a comparative analysis of the works of foreign writers.